Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Media Animasi Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Fisika Siswa SMAN 5 Mataram Tahun Ajaran 2016/2017 - Haris Munandar; Sutrio Sutrio; Muhammad Taufik (Department of Physics Education, Universitas Mataram, 2018)
Abstract Ã¢â¬â The aim of this research is to know the impact of the applying of problem-based learning with animation toward the critical thinking skill and result of learning physics of student of SMAN 5 Mataram academic year 2016/2017. This research is belong to quasi experiment with pretest-postest control group design. The population is all student of XI MIPA at SMAN 5 Mataram, while the sample are class XI MIPA 4 as the experimental class, and the XI MIPA 6 as control class. The sample taken by the random sampling. The collect of data is done by give the test, 20 multiple choice to knowing the result of learning phyisics and 5 essay for knowing the studentÃ¢â¬â¢s critical thinking skill. The collected data has been analyzed by using the -test. The result of this research shows that (1) there is an impact of the applying of problem-based learning with animation toward the studentÃ¢â¬â¢s critical thinking skill that includes the ability in: (a) focusing the question, (b) analyzing the argument/identificating the reason, (c) inducing and considering the result of induction, (d) evaluating the result of consideration, (e) giving the reason; (2) there is an impact of the applying of problem-based learning with animation toward the studentÃ¢â¬â¢s result of learning physics that includes the result of learning in the cognitif area that follow the BloomÃ¢â¬â¢s taxonomy, that is C1 till C6 (remembering, knowing, applying, analyzing, evaluating, and creating).